Bridging Technology and Pedagogy: A Qualitative Study of Deep Learning-Based Hybrid Learning in English for Business - Restu Januarty Hamid; Rampeng Rampeng; Rosmawati Abdul Maing; Asdar Asdar (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
This study investigates how deep learning–based artificial intelligence (AI) can effectively support hybrid learning in English for Business courses. In response to rapid technological change in higher education, the research explores how digital tools can complement human teaching and learning. Using a qualitative case study design, data were collected from 10 lecturers and 15 students through interviews, classroom observations, and document analysis. The findings reveal that AI-enabled features, such as personalized learning paths, instant feedback, and gamified activities, enhanced students’ motivation, supported self-paced learning, and improved awareness of individual strengths and weaknesses. However, participants also reported challenges, including limited digital literacy, unstable internet access, and difficulty managing multiple platforms. Importantly, both lecturers and students emphasized that human interaction remains crucial, with real-time discussion, collaborative activities, and instructor guidance playing key roles in developing confidence and business communication skills. The study concludes that successful AI-enhanced hybrid learning requires not only technological innovation but also strong institutional support and thoughtful pedagogical practice. AI should be viewed as a complementary tool rather than a replacement for the human connections essential to meaningful language learning.